The Impact of Students' Learning Interests and Parenting Patterns on Economic Learning Outcomes - Sujana, I Nyoman; Dharmayasa, I Putu Arya; Ardiani, Ni Wayan Desi (Mimbar Ilmu, 2024)
The lack of parental attention to children's character education makes parents' parenting patterns less than optimal, so children's interest in learning decreases, which causes student learning outcomes not to meet the KKM at school. Therefore, this research aims to partially and simultaneously examine the influence of learning interests and parenting patterns on the economic learning outcomes of class XI students. This type of research is causal research. The population in this research was 107 students, and the sample used was 84 students. Data collection methods using questionnaires and documents were analyzed using multiple linear regression. Hypothesis testing using the t-test and F-test was processed using the SPSS 20.0 for the Windows program. This research shows that interest in learning and parenting patterns partially and simultaneously influence students' social studies learning outcomes, which are expressed at a significance level of 0.000 <0.05. Based on this, it is concluded that formal education must also be balanced with informal education provided by parents through good parenting. This will increase students' interest in learning so that student learning outcomes will improve. This research provides theoretical implications that the solution to increasing student interest in learning and learning outcomes can be done by applying informal education to balance formal education.